Perilaku Manajemen Diri dan Profil Temperamen pada Karyawan Universitas Prediabetes: Studi Kuantitatif Deskriptif - Barita Juliano Siregar; Almahdy A; Dedy Almasdy; Ofa Suzanti betha; Edi Rohaedi; Rafly Syah Putra (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2025)
This descriptive study (n = 39) investigated diabetes self‑management Questionnaire (DSMQ) and temperament profiles among university employees with prediabetes risk. DSMQ subscales (glucose management, dietary control, physical activity, healthcare use) were assessed alongside 75‑g OGTT categories (IFG/IGT) using ADA‑standard definitions. Most participants had low DSMQ scores (79.5%), with dietary control and physical activity as the weakest domains. Overweight/obesity was highly prevalent (BMI ≥ 23 kg/m²; 85%), and routine check‑ups were infrequent. BMI correlated with prediabetes (r = 0.436; p = 0.005) and hypertension (r = 0.466; p = 0.003). Dominant temperament was associated with 2‑hour plasma glucose during OGTT (ρ = 0.321; p = 0.045), whereas subdominant temperament was not significant (ρ = 0.285; p = 0.071). We clarified DSMQ structure (16 items; reverse‑coded items; sum scale) and standardized IFG/IGT/75‑g OGTT terms in line with ADA 2025. Findings highlight the need for workplace multicomponent programs integrating nutrition education, structured physical activity, weight management, and temperament‑informed counseling. Limitations include descriptive design (n = 39), purposive sampling, potential confounding, and the non‑causal nature of correlations. In settings with low health service utilization, pragmatic screening and regular follow‑up combined with personalized behavior change strategies may help prevent progression to type 2 diabetes.